(untitled) (Baghdad Science Journal, 2004)
thirty adult NewZealand rabbits used in this study, they were divided in to two groups (control and treaded with Helium — Neon laser). A square skin flap done on the medial aspect of the auricle of both sides, a square piece of cartilage incised, pealed out from each auricle and fixed in the site of the other, then the flaps sutured .The site of the operation in the rabbits of the treated group were irradiated using a Helium —Neon laser with (5mw) power for (10 days) began after the operation directly, (3 rabbits) from each group used for collection of specimens for histopathological examination at the weeks (1,2,3,4, & 6) weeks post the operation .The results revealed Early invasion of the matrix with elastic fibers which continue to the surrounding perichondrium, mature lacunae and complete healing occurred later at the 6th week in the treated group. Conclusion: Helium- Neon laser raised the mitotic activity of the cartilage cells, activated the reproduction processes in addition to the intra and extra regenerative reparation.